Ground displacements on Bouvet Island using SAR Interferometry (18/2018) - Rouyet, Line; Lauknes, Tom Rune; Larsen, Yngvar; Norut (2018)
Based on 8 RADARSAT-2 Ultrafine scenes from December 2017 to June 2018, ground displacements close to the Norvegia research station of Bouvet Island have been measured using Synthetic Aperture Radar Interferometry (InSAR). The results show that loss of coherence related to erosion processes is affecting the coast west from the station. The mean velocity maps identify a well-defined unstable area south from Norvegia and by applying the Small Baseline Subset (SBAS) time-series InSAR method, we are able to provide time series during the considered time period. The results tend to indicate that the area north from the current location of Norvegia station is more stable.
Keywords: Bouvetøya; geovitenskap; interferometri

Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi